BUD ROT DISEASE ON PB 121 COCONUT AT BANGUN PURBA PTP VI, NORTH SUMATRA - J. Brahmana; Azis Kelana (International Coconut Community Journal, 1988)
Three‑year observations made upto 1987 on coconut hybrid PB121 (Malayan Yellow Dwarf x West Affican Tall) planted at the Bangun Purba PTP VI Estate, North Sumatra in 1977 revealed a 9.5 percent infestation by bud‑rot disease. Bud‑rot is disastrous since it kills the only growing point of the plant, and until today no remedy has been found out other than uprooting and destroying the diseased palms. Exast cause of but‑rot is not known, eventhough the fungus Phytophthora palmivora is associated with the affected palms. This disease is noticed exclusively on mature palms, older than four years, and is found to spread blockwise.